Functional outcome of arthroscopic subacromial decompression in shoulder impingement syndrome - Dina, Twahir Kalekhan; Aziz, Sobia; Sufyan, Muhmmad; Muhammad Kazim; Shah, Sayed Moinuddin; Noor, Syed Shahid (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the outcomes of arthroscopic subacromial decompression in the treatment of shoulder impingement syndrome cases, and to identify patient factors favouring selection for the intervention. Method: The retrospective study was conducted in the Department of Orthopaedic Surgery, Liaquat National Hospital, Karachi, and comprised data from January 2018 to December 2023 of male and female patients diagnosed with chronic shoulder impingement syndrome with Neer stage 1-III and Bigliani types I-III. Demographic and clinical history as well as Oxford Shoulder Score and Satisfaction Score were noted using a proforma. The scores at baseline were compared with those taken at the 12-month follow-up. Data was analysed using SPSS 25. Results: Of the 72 patients with mean age 43.24±12.5 years, 49(68%) were female and 23(%32%) were male. There were 60(83.3%) patients with intact rotator cuff, and 12(16.6%) with rotator cuff fibrillation without tear. There was significant improvement at the follow-up compared to baseline shoulder and satisfactions scores (p<0.05). Patients with Bigliani type II or III acromion at baseline showed significantly more improvement than those with type I (p<0.05). Conclusion: Arthroscopic subacromial decompression provided substantial benefit to patients with shoulder impingement syndrome. However, patient selection for such an intervention was found to be a critical factor. Key Words: Shoulder impingement syndrome, Arthroscopic subacromial decompression, Oxford Shoulder Score.